Traditionally used herbal medicines with antibacterial effect on Aggegatibacter actinomycetemcomitans: Boswellia serrata and Nigella sativa - Bita Maraghehpour; Mina Khayamzadeh; Shamsoulmolouk Najafi; Mohammadjavad Kharazifard (Wolters Kluwer Medknow Publications, 2016)
Background: Since bacterial strains developed resistance against commonly used antibiotics and side effects became more serious, other alternatives have been postulated. There is an answer for this issue in ancient medicine. Many plants have been proved to provide antibacterial effect. In this study, Boswellia serrata (BS) and Nigella sativa (NS) were assessed to evaluate the antibacterial effect on Aggregatibacter actinomycetemcomitans (A.a) known as main pathogen of aggressive periodontitis. Materials and Methods: Broth microdilution method was used to obtain minimum inhibitory concentration (MIC) of crude extract of BS and NS. Furthermore, the logarithm of colony forming units grown in fresh brain heart infusion bacterial culture was assessed. Three groups including BS+ (containing only BS), NS+ (containing only NS), and BS-NS− (control group) were defined. For each group, the experiment was repeated 12 times. Results: MIC of BS and NS were 512 μg/mL and 128 μg/mL, respectively. No growth was observed in our negative control group. The mean ± standard deviation of logarithm of CFU/mL for BS, NS, and control group was 4.32 ± 0.36, 3.61 ± 0.3, and 5.57 ± 0.19, respectively. ANOVA test revealed significant difference (P values < 0.0001) of these groups which was later confirmed using the post hoc test of Tukey's honest significant difference (all sP < 0.0001). Conclusions: Both BS and NS are effective against A.a which should be taken into account as appropriate ingredient for oral hygiene products.